(untitled) (Ukrainian Journal of Ophthalmology, 2026)
In most countries, the uveitides are responsible for 5-13% of all cases of blindness. Non-infectious uveitides are divided into those with and without known systemic association (both in children and adults). The Standardization of Uveitis Nomenclature (SUN) Working Group used anatomic location of the inflammation as an ontologic dimension, defined the criteria for the activity of inflammatory process, divided uveitis into groups and subgroups based on its course, and defined the tactical treatment algorithm. The uveitis development is based mainly on the alterations in the mechanisms of immunotolerance toward self ocular antigens, and on the emergence of autoagression toward these antigens. An alteration in immune tolerance to ocular antigens occurs if (1) regulatory CD25 + T cell subset is insufficient, and (2) B cells are activated with production of specific antibodies to the uveal tract structures. Systemic therapeutical agents for uveitis include corticosteroids, nonsteroidal anti-inflammatory drugs, cytostatics and immunobiologic agents. There are, however, no clinical guidelines involving the uveitis treatment approaches listed. The analysis of correlations between the degree of the alterations in the immune system and the course of uveitis will allow the development of the algorithm for the treatment of uveal inflammation entities.